Evaluation of Dialysis Efficiency for Renal Failure Patients in Libya’s Southern, Ubari Region - Annuor M. Alalem; Embarka Rajab Ahmed; Abdel Hakim Abdel Salam Al Wafa; Al Zahra Barkani Abdel Salam; Ali MB Nouh (Journal of Medical Sciences, 2022)
Kidney disease is one of the most common causes of kidney failure in the world. Dysfunctional kidneys cannot effectively eliminate harmful toxins and maintain normal body functions. To eliminate accumulated toxins, individuals suffering from this condition undergo hemodialysis or peritoneal dialysis. This study aimed to evaluation of the effectiveness of dialysis in removing toxins, as well as the effects of hemodialysis on electrolytes and biochemical substances. Method: 24 haemodialysis patients were recruited from the Ubari region in the south of Libya. Blood samples were collected before and after dialysis and analysis of blood biochemical, haemotoligical and electrolytes parameters. In each patient, the average concentrations of these parameters and the rate of urea decline were calculated. Results: It showed in Al-Tanahma Dialysis Unit, WBC and MCHC, urea, creatinine, uric acid, and potassium concentrations were significantly different (P<0.05) before and after hemodialysis. Hb, RBC, Hct, MCV, MCH, PLT, CL-, and Na+ before and after hemodialysis showed no significant differences. In the Ubari Dialysis Unit, there are significant differences (P<0.05) before and after hemodialysis in Hb, RBC, Hct, Na+, K-, urea, creatinine, and uric acid. No significant differences in MCV, MCH, MCHC, WBC, PLT, and CL- before and after hemodialysis. Most patients (71.4%) in the Al-Tanahma Unit had urea decline rates under 65%, and 28.6% had urea decline rates over 65%. In the Ubari Unit, half of the patients (50%) had a rate under 65% and (50%) were rated higher than 65%. Conclusion, both units, as well as each patient, was found to be ineffective with hemodialysis. A comparison of similar studies with several dialysis units in this area will allow us to determine factors that contribute to the ineffectiveness of dialysis in kidney disease patients.